Immersive Encounters: A Journey Through the Helsinki Biennial 2023 (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2024)
This article provides a comprehensive analysis of the Helsinki Biennial 2023, focusing on its thematic explo- ration of contemporary environmental issues, artistic medi- ation, and the intersection of art with ecological and social concerns. Drawing from a range of artworks exhibited at the biennial, including installations, sculptures, and video pre- sentations, the analysis explores themes of contamination, regeneration, and agency within the context of contemporary environmental discourse. The article highlights the immersive nature of the biennial, both in its physical setting on Vallisaari Island and in its conceptual framework, which encourages visitors to engage deeply with the environment and the art- works. Through a nuanced examination of selected artworks, the article elucidates how artists employ various media and methodologies to convey complex narratives about the in- terplay between human-nature relationships, environmental justice, and the urgent need for collective action in the face of global environmental challenges.
Keywords: Environmental art; Artistic mediation; Environmental justice; Immersive experience; Ecological narratives